Identifying Collapsible Soils from Seismic Cone (SCPT): A Qualitative Approach - Rocha, Breno Padovezi; Silveira, Isabela Augusto [UNESP]; Rodrigues, Roger Augusto [UNESP]; Lodi, Paulo Cesar [UNESP]; Giacheti, Heraldo Luiz [UNESP] (MDPI, 2023)
Collapsible soils are unsaturated low-density soils that undergo abrupt settlement when flooded without any increase in the in-situ stress level. The first stage of the site characterization is identifying collapsible soils, since these are problematic soils. Seismic cone testing (SCPT) has been increasingly used for site characterization, because it allows combining stratigraphic logging with the maximum shear modulus (G0) determination. In this paper, laboratory and in-situ tests carried out at 21 sites with collapsible and non-collapsible soils are interpreted to differentiate between such soils, based on the seismic cone test (SCPT). Collapsible soils have G0/qc values greater than 23 and qc1 values less than 70, while non-collapsible soils have G0/qc values less than 23 and qc1 values greater than 70. The investigated collapsible soils have microstructure (bonding/cementation), but the classical approach cannot be sufficient to identify collapsible soils alone. An approach was used to identify collapsible soils based on maximum shear modulus (G0), normalized cone resistance (qc1), and cone resistance (qc). The chart G0/qc versus qc1 and boundaries is an alternative for distinguishing between collapsible and non-collapsible soils in the early stage of site investigation. This qualitative approach should be used in the preliminary investigation phase to select potentially collapsible soils and helps guide the sampling of potentially collapsible soils for laboratory testing. Further SCPT data from different soil types, particularly the collapsible ones, are valuable to adjust or confirm the boundary equations suggested.
Keywords: collapsible soils; G0/qc ratio; identification; seismic cone; small-strain stiffness